2016
DOI: 10.1155/2016/8458696
|View full text |Cite
|
Sign up to set email alerts
|

Development of Cardiovascular Indices of Acute Pain Responding in Infants: A Systematic Review

Abstract: Background. Cardiovascular indices of pain are pervasive in the hospital setting. However, no prospective research has examined the development of cardiac responses to acutely painful procedures in the first year of life. Objectives. Our main goal was to synthesize existing evidence regarding the development of cardiovascular responses to acutely painful medical procedures over the first year of life in preterm and term born infants. Methods. A systematic search retrieved 6994 articles to review against inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 76 publications
2
20
0
Order By: Relevance
“…However, some individuals demonstrate an uncoordinated relationship between these stress response systems, when one response compensates for another [ 25 , 26 , 27 ]. In older infants, the autonomic nervous system and HPA response are not always coordinated at an individual level, in keeping with research on adults [ 28 , 29 ] and the results reported here.…”
Section: Discussionsupporting
confidence: 91%
“…However, some individuals demonstrate an uncoordinated relationship between these stress response systems, when one response compensates for another [ 25 , 26 , 27 ]. In older infants, the autonomic nervous system and HPA response are not always coordinated at an individual level, in keeping with research on adults [ 28 , 29 ] and the results reported here.…”
Section: Discussionsupporting
confidence: 91%
“…For these particularly premature children, we established marked physiological changes during provoked acute pain. First of all, we found significantly increased HR by more than 10 bpm ( p < 0.001) between basal state and painful state, illustrating that HR is a sensitive marker of neonatal pain frequently used in studies (Lindh et al., ; Oberlander et al., , ; Grunau et al., ; Waxman et al., ) and integrated in several pain assessment scales, such as the PIPP‐R and COMFORT scales. However, HR is not specific of pain and cannot be used alone as a pain marker.…”
Section: Discussionsupporting
confidence: 60%
“…() showed increased HF and LF and paradoxical decrease in the LF/HF ratio during a painful event. A recent systematic review reported the great heterogeneity among results about frequency indices of HRV during acute pain in preterm neonates (Waxman et al., ). Part of them showed decreased HF, unlike others (Lindh et al., , ; Gormally et al., ; Greenberg, ; Oberlander et al., ; Weissman et al., ; De Oliveira et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Additional analyses. Only approximately half of the studies (12/22) included in our review measured and adjusted for key potential confounding variables that are known to impact physiology (i.e., age, sex, baseline characteristics, time of day, activity level, and respiration; Oberlander & Saul, 2002;Waxman et al, 2016). Moreover, the covariates and moderators used were not consistent across studies and included child-level (i.e., sex, age, baseline HR, and activity) and dyad-level (i.e., attachment, early adversity) factors.…”
Section: Methodological Challengesmentioning
confidence: 99%